BipA: a tyrosine‐phosphorylated GTPase that mediates interactions between enteropathogenic Escherichia coli (EPEC) and epithelial cells - Michele Farris; Andrew J. Grant; Tobias B. Richardson; C. David O′Connor (1998)
We report the functional characterization of BipA, a GTPase that undergoes tyrosine phosphorylation in an enteropathogenic Escherichia coli (EPEC) strain. BipA − mutants adhere to cultured epithelial cells but fail to trigger the characteristic cytoskeletal rearrangements found in cells infected with wild‐type EPEC. In contrast, increased expression of BipA enhances actin remodelling and results in the hyperformation of pseudopods. BipA appears to be the first example of a new class of virulence regulator, as it also controls flagella‐mediated cell motility and resistance to the antibacterial effects of a human host defence protein. Its striking sequence similarity to ribosome‐binding elongation factors suggests that it uses a novel mechanism to modulate gene expression.